MUTASI APARATUR SEBAGAI INSTRUMEN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN KINERJA PEMERINTAHAN DAERAH - Pratama, Ivan Yoga; Setyowati, Yuli (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study examines the role of apparatus mutation as an instrument of public sector human resource management in improving local government performance. The issue of mutation in regional bureaucracy is often associated with administrative routines and political considerations, while its strategic function in strengthening organizational performance has not been optimally explored. This study aims to analyze how mutation mechanisms contribute to improving government performance from a conceptual and managerial perspective. The research employs a qualitative approach using a literature review method by analyzing scientific articles, academic books, and policy documents published within the last ten years. Data analysis was conducted through thematic analysis and critical synthesis of relevant literature related to public human resource management, bureaucratic reform, and government performance. The results of the study indicate that apparatus mutation can function as a strategic human resource management instrument when implemented based on competence, performance evaluation, and organizational needs. Properly managed mutations are able to enhance employee motivation, improve job–person fit, and strengthen bureaucratic professionalism, which in turn supports better government performance. Conversely, non-transparent and non-merit-based mutation practices tend to weaken organizational effectiveness and reduce public trust. This study concludes that apparatus mutation should be positioned as a strategic managerial policy rather than merely an administrative procedure. Strengthening merit-based systems and institutional commitment is essential to ensure that mutation policies contribute positively to local government performance.